S.I.R.I.A. - The Information System of Italian Research in Antarctica - Di Bono, Maria Grazia; Martinelli, Massimo; Salvetti, Ovidio; Benedetti, E.; Castorina, Mario; Damiani, A.; Piervitali, E.; Rafanelli, C. (2003)
Metadata provides descriptive information that characterizes a set of quantitative and/or qualitative measurements collected. It is the primary mechanism for documenting data and instruments involved in data collection. The paper explains the structure and the activity of Information System Italian Research in Antarctica Project (SIRIA) the Italian metadata project to collect and disseminate the information on Italian research in Antarctica